2004
DOI: 10.1089/154099904322966146
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Metabolic Syndrome among Young Women with Nonfatal Myocardial Infarction

Abstract: Although this study may have been underpowered to recognize the contribution of other risk factors, we found that the dominant predictor of nonfatal MI in young women was the MetS. Screening young women with central obesity for other parameters of the MetS may help reduce the risk of MI at an early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
2
4
0
1
Order By: Relevance
“…With our study we infer that hypertension and fasting hyperglycemia are the most prevalent components of metabolic syndrome in patients of acute coronary syndrome low HDL level was the least frequent one this was in similarity of studies done by Amowitz et al 9 Tenerz A, et al 11 and Zeller M, et al 2 Metabolic syndrome is more common in patients having fasting hyperglycemia. Impaired glucose tolerance is one of the commonest components of metabolic syndrome in patients with coronary artery disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With our study we infer that hypertension and fasting hyperglycemia are the most prevalent components of metabolic syndrome in patients of acute coronary syndrome low HDL level was the least frequent one this was in similarity of studies done by Amowitz et al 9 Tenerz A, et al 11 and Zeller M, et al 2 Metabolic syndrome is more common in patients having fasting hyperglycemia. Impaired glucose tolerance is one of the commonest components of metabolic syndrome in patients with coronary artery disease.…”
Section: Discussionsupporting
confidence: 88%
“…As in previous studies by Zeller M, et al 2 and Amowitz LL, et al 9 in our study, out of 55 patients 28 patients (51%) had metabolic syndrome while the rest 21 patients (49%) did not have Metabolic Syndrome.…”
Section: Discussionsupporting
confidence: 86%
“…The utility of the metabolic syndrome concept for risk stratification in the young non-pregnant population [29] and the observed similarities between CVD and pre-eclampsia suggest its potential usefulness in the pregnant population. This association between pre-eclampsia and metabolic syndrome is stronger than the association with CHTN or lipids alone suggesting an added benefit to the aggregate syndrome concept over individual risk factors alone.…”
Section: Discussionmentioning
confidence: 99%
“…13 They found that when compared with female controls matched for age, ethnicity, and smoking, the cases were more likely to have insulin resistance, obesity, dyslipidemia, and hypertension. Interestingly, there was no statistically significant difference in the levels of inflammatory and thrombotic biomarkers; however, the study may have been underpowered to accurately assess these associations.…”
Section: Background and Definitionmentioning
confidence: 99%